A case control study of lifestyle factors in the aetiology of ovarian cancer - Su, Dada (Curtin University, 2013)
This case-control study investigated associations between ovarian cancer and lifestyle factors among Southern Chinese women in Guangzhou, China. The investigation mainly focused on the effects of tea consumption, physical activity, breastfeeding and body size on the risk of ovarian cancer. The findings suggest regular tea consumption, physical activity and prolonged lactation are associated with reduced risk of ovarian cancer. Higher body weight and higher BMI levels were associated with increased risk of ovarian cancer.